Regresi Ambang untuk Mendalami Pengaruh Nonlinier Kekuatan Pasar terhadap Pinjaman Bank di ASEAN-5 - Ekananda, Mahjus (UI Scholars Hub, 2023)
Credit distribution has developed rapidly in the ASEAN region and it is largely dominated by the banking sector compared to other financial institutions. This study explores the effects of various changes to the GDP growth regime, firm size, and monetary policy. The objects of this research are commercial banks in ASEAN-5 from year 2010 to 2019. This study utilises the threshold regression method and a single proxy to measure market power. Results of this study found that monetary policy and market forces affect productive credit. Changes in impact that occur are mostly due to different behavior between banks in response to different regulations. In addition, the response of economic actors differs on different levels of GDP growth and monetary policies.